CD56bright NK cells are enriched at inflammatory sites and can engage with monocytes in a reciprocal program of activation - Dalbeth, N; Gundle, R; Davies, R; Lee, Y; Mcmichael, A; Callan, M (2004)
Human NK cells may be divided into a CD56dim subset and a CD56bright subset. In peripheral blood, CD56dim NK cells dominate, whereas in lymph nodes, CD56bright NK cells are more common. In this study we show that CD56bright NK cells accumulate within inflammatory lesions in a wide variety of clinical diseases affecting several different anatomical sites. We demonstrate that when activated by the monokines IL-12, IL-15, and IL-18, these NK cells promote TNF-α production by CD14+ monocytes in a manner that is dependent on cell:cell contact Conversely, CD14+ monocytes synergize with monokines to promote IFN-γ production by these NK cells. Again, this interaction is dependent on cell:celll contact The experiments show that CD56bright NK cells accumulate in inflammatory lesions and, in the appropriate cytokine environment, can engage with CD14+ monocytes in a reciprocal activatory fashion, thereby amplifying the inflammatory response. Such a positive feedback loop is likely to be important in the pathogenesis of chronic inflammatory conditions such as rheumatoid arthritis.